Penyuluhan Pemberdayaan Masyarakat melalui Media Paving Block untuk Menunjang Aksesibilitas Masyarakat (Desa Morong, Kecamatan Sungai Lala Kabupaten Indragiri Hulu, Riau) - Sry Windartini; Nedra Neswita; Sri Agustin; Adriansyah Adriansyah; Sri Guntur (Jurnal Kabar Masyarakat, 2023)
Community empowerment is a process of developing opportunities, willingness/motivation and ability of the community to be able to access resources, thereby increasing their capacity to determine their own future by participating in influencing and realizing the quality of life for themselves and their groups. This counseling activity aims to empower the community through paving block media to support community accessibility and can improve the local village economy and can be continued in the coming year at the local location or in other areas that have the same characteristics. The community was enthusiastic and very positive in participating in this counseling as seen from their many questions and curiosity from the counseling regarding the materials and tools to be used if they wanted to open a community-based home business/industry.